Fracture of the acetabulum with femoral artery injury presenting late: A case report. (February 2016) - Kalyanasundaram, Sivaprasad; Menon, Venugopal K.; Varughese, Jacob; Hassan, Yasser Abbas Anis
Abstract: This study reports a rare case of both column acetabulum fracture with femoral artery injury that presented late and was managed with arterial reconstruction and fracture fixation. A thirty-one year old man sustained both column acetabular fracture on the left in a motor vehicle accident. On admission there was no obvious neuro-vascular deficit. During surgery for the fracture after 7 days of the injury the femoral artery was found to be severely crushed with no blood flow. The anterior column of the acetabulum was stabilised followed by resection and reconstruction of the femoral artery. The post-operative period was uneventful and he was discharged normally. At 6 months from injury the fractures had united well with excellent limb circulation and good lower limb function. Femoral artery injury with acetabular fracture is rare and late presentations are unreported hitherto. The results of fracture stabilisation and vessel reconstruction seem to be excellent. Literature of similar injuries is reviewed.